A descriptive case study of grieving beliefs in a hospital setting: implications for advance care planning and end of life. Issue 2 (1st June 2012) - Sexton, C
Abstract : A major activity and concern in end of life care is bereavement risk assessment of the patient's carer and family members. The assessments and conceptualisations of the grieving process are based on studies of adults in clinical settings after death of the loved one. This study collected data about grieving from an adult lay population (N=312) in a hospital setting. There were statistically significant differences between male and female views of grieving. Male responses to 3 items demonstrate sensitivity to emotional and relational aspects of adapting to loss. This study builds on prior research of gender differences by providing data about those differences. The findings point to a critical need for helping and health care professionals to educate carers and families about the distinction between grieving and depression. Early, timely interventions such as this are part of the preparatory processes that lead to positive bereavement outcomes. This study is the first empirical research of adults' view of grieving in a hospital setting in the U.S.